Ruthenian Exposition of the Kievan Caves Paterikon in the Manuscript Small Bible by Gregory Dmytriyevych (Sharhorod, 1660): Publication - Temčinas, Sergejus (Slavistica Vilnensis, 2025)
The abridged exposition of selected articles of the Kievan Caves Paterikon in the manuscript entitled Small Bible and written by the Orthodox priest Gregory Dmytriyevych in Sharhorod in 1660 (Moscow, Russian State Library, V. M. Undolskiy collection (f. 310), No. 527, fol. 236v–240v; 241v– 242v), is published in full.